Severe acute respiratory syndrome coronavirus envelope protein ion channel activity promotes virus fitness and pathogenesis - Verdiá-Báguena, Carmina (2014)
Deletion of Severe Acute Respiratory Syndrome Coronavirus (SARS-CoV) envelope (E) gene attenuates the virus. E gene encodes a small multifunctional protein that possesses ion channel (IC) activity, an important function in virus-host interaction. To test the contribution of E protein IC activity in virus pathogenesis, two recombinant mouse-adapted SARS-CoVs, each containing one single amino acid mutation that suppressed ion conductivity, were engineered. After serial infections, mutant viruses, in general, incorporated compensatory mutations within E gene that rendered active ion channels. Furthermore, IC activity conferred better fitness in competition assays, suggesting that ion conductivity represents an advantage for the virus. Interestingly, mice infected with viruses displaying E protein IC activity, either with the wild-type E protein sequence or with the revertants that restored ion transport, rapidly lost weight and died. In contrast, mice infected with mutants lacking IC activity, which did not incorporate mutations within E gene during the experiment, recovered from disease and most survived. Knocking down E protein IC activity did not significantly affect virus growth in infected mice but decreased edema accumulation, the major determinant of acute respiratory distress syndrome (ARDS) leading to death. Reduced edema correlated with lung epithelia integrity and proper localization of Na+/K+ ATPase, which participates in edema resolution. Levels of inflammasome-activated IL-1β were reduced in the lung airways of the animals infected with viruses lacking E protein IC activity, indicating that E protein IC function is required for inflammasome activation. Reduction of IL-1β was accompanied by diminished amounts of TNF and IL-6 in the absence of E protein ion conductivity. All these key cytokines promote the progression of lung damage and ARDS pathology. In conclusion, E protein IC activity represents a new determinant for SARS-CoV virulence.